Some Reflections on the Evolution of International Sustainability Law - Fernández Liesa, Carlos R. (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This contribution involves a reflection on the notion of sustainability and its relevance for the international order. As it is an indeterminate notion, it is relevant to approach it in order to see to what extent it is reflected in general and particular legal obligations and whether it is possible to speak of an international law of sustainability. In any case, the current geopolitical and economic context is not very positive, nor is the crisis of multilateralism and international institutions in an international law in transition.